1994
DOI: 10.1038/ki.1994.342
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for abnormal calcium homeostasis in patients with adynamic bone disease

Abstract: To investigate whether the derangements in calcium kinetics in patients with renal osteodystrophy are similar in the various histologic forms of this metabolic bone disease, 43 patients on chronic maintenance dialysis underwent calcium kinetic studies using the double isotope technique, iliac crest bone biopsies for mineralized bone histology and histomorphometry and determinations of serum indices of calcium and bone metabolism. Intestinal calcium absorption was not different among the three histologic groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
156
0
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(167 citation statements)
references
References 23 publications
4
156
0
7
Order By: Relevance
“…Our data are in accordance with previous Ca kinetic studies of maintenance dialysis patients that showed a significant and direct relationship between serum PTH levels and plasma Ca efflux (24).…”
Section: Discussionsupporting
confidence: 82%
“…Our data are in accordance with previous Ca kinetic studies of maintenance dialysis patients that showed a significant and direct relationship between serum PTH levels and plasma Ca efflux (24).…”
Section: Discussionsupporting
confidence: 82%
“…Low bone turnover is not merely a histologic entity; it also has important clinical ramifications. Patients with low bone turnover have abnormal calcium homeostasis, (12) and it was shown that low bone turnover is associated with vascular calcifications. (27) The study also shows that white patients are more likely to present with low bone turnover than blacks.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormalities encompass changes in bone turnover (T), mineralization (M), bone balance and the result of it, which is bone volume (V). Clinically, disorders in bone turnover (T) are associated with disturbed mineral homeostasis (12,13) and increased fracture risk. (14) Defective mineralization (M) may result in bone pain and/or fracture.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Evidence derived from classic clinical radiolabel studies suggests that the inability of bone to serve as a buffer for excess calcium and phosphate contributes to serum phosphate elevations and may lead to deposition of excess mineral in soft tissues. 31,32 We therefore determined the effect of Npt2b deletion on bone disease in the adenine mouse model. Classic features of high turnover, including increased bone formation rates, elevated mineral apposition rates, and increased osteoid surface, were observed in uremic mice as an apparent consequence of elevated PTH (Figure 6).…”
Section: Discussionmentioning
confidence: 99%